Density functional theory calculations of the non-resonant and resonant X-ray emission spectroscopy of carbon fullerenes and nanotubes - Hanson-Heine, Magnus W.D.; George, Michael W.; Besley, Nicholas A. (Elsevier, 2018)
The non-resonant X-ray emission spectroscopy of fullerenes and carbon nanotubes is studied with density functional theory in conjunction with short-range corrected functionals. For C60 and C70 the X-ray emission spectra are insensitive to modest structural changes, and absorption onto the fullerene cage has the greatest effect with a broader less structured band observed with the high energy ⇡ band reduced in intensity. For carbon nanotubes the X-ray emission spectra are shown to be weakly dependent on the length and chirality of the nanotube. However, some variation with the diameter of the tube is observed in both resonant and non-resonant spectra.